IMPLEMENTASI SUPERVISI AKADEMIK UNTUK MENINGKATKAN KOMPETENSI PEDAGOGIK GURU TK NEGERI PEMBINA BATU AMPAR - Yovi Yanti; Marinu Waruwu; Halida; Eny Enawaty; Mery Monalisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to analyze the role of supervisors in implementing academic supervision to improve the pedagogic competence of Pembina Batu Ampar State Kindergarten teachers. The focus of this research is on the role of supervisors in increasing teacher competency through academic supervision and the quality of education. The method used is a qualitative approach, data collection is carried out through interviews, observation and documentation. Data analysis was carried out by the Miles and Hubernes Model which consists of data condetation, data display, and conclusion drawing verification. The research results show that the role of supervisors in academic supervision is important to improve teachers' pedagogical competence, because supervisors can act as partners, innovators, consultants, and motivators. This role is carried out to improve the pedagogical competence of teachers at the Pembina Batu Ampar Kindergarten.